Contributions to a hermeneutical phenomenology of the mystic - González Suárez, Lucero (Estudios de Filosofía, 2013)
The purpose of this reflection is to present some original contributions, from an ontological perspective, for the implementation of the phenomenological method to the interpretation of mystical testimonies. According to the first Heidegger, but trying to overcome its deficiencies, I propose some guidelines for the development of a hermeneutic phenomenology of mysticism, through the interpretation of those texts where the essential features of mysticism, as a modality of factual life, are expressed.